PENGEMBANGAN MEDIA VIDEO ANIMASI SEBAGAI PENCEGAHAN DIABETES MELITUS TIPE 2 PADA REMAJA KELAS XI - Salsabila, Raden Roro Fadilah; Lestari, Febri Sri (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: In 2022, there were 44,329 persons with diabetes mellitus in the city of Bandung and Coblong District with 2,032 people with diabetes mellitus. This is a lack of an unhealthy lifestyle. Therefore, the overcoming of the problem of diabetes mellitus can be done through health promotion about the prevention of type 2 diabetes mellitus through animated videos that have novelty of material with 3 healthy steps to prevent type 2 diabetes mellitus that are informative, varied characters, and duration, so that they can convey information that attracts the attention and focus of students. Objective: To develop animated video media as a prevention of type 2 diabetes mellitus in adolescents in grade XI with 4D development (Define, Design, Development, Disseminate). Methods: This research included R&D applying a 4D model. The research subjects were taken by probability sampling technique of 78 teenagers in class XI at SMAN 19 Bandung. Results: The material feasibility test by material experts showed a result of 93.75%%, media experts 100%, and media users 96% with a very feasible category. Conclusion: Animated video media is declared very feasible to be used as a prevention of type 2 diabetes mellitus in adolescents in grade XI.